3D scanning of a carburetor body using COMET 3D scanner supported by COLIN 3D software: Issues and solutions. (2021) - Haleem, Abid; Gupta, Pawan; Bahl, Shashi; Javaid, Mohd; Kumar, Lalit
Abstract: Nowadays, the industry uses 3D Scanners for reverse engineering, new product design, rapid manufacturing, multimedia, architecture, inspection, and quality control. The scanning process converts a real object into a digital format. This paper's essential purpose is to show the use of a 3D blue light Scanner/COMET 3D to redesign a carburetor body. The paper identifies different issues involved in the processes to help future users. COMET 3D does scanning of the carburetor body by which COLIN 3D software is used for measurements, editing, and analyzing of the acquired point clouds data. This paper also identifies the necessary steps to undertake 3D Scanning and part dimensioning for a carburetor body. It also discusses the error/problems that occurred during the process. The applications of non-contact blue light 3D Scanners are many as they can be innovatively used to redesign an existing part, architecture designing, and reducing production cycle time, biomedical and associated applications. This paper's contribution lies in achieving a step-by-step procedure of scanning any three-dimensional object as this helps in understanding the 3D scanning hardware and support software. It provides good knowledge of how to resolve the issues that can cause an error during the measurement of the surfaces and scan objects.